Comparison of cardiogenic NEC and classical NEC in the fourth level neonatal intensive care center - Tülin Öztaş; Salim Bilici; Nilüfer Matur Okur (SpringerOpen, 2023)
Abstract Background The most common inflammatory gastrointestinal disorder in newborn infants is necrotizing enterocolitis (NEC). Despite the multifactorial etiology of NEC, its pathogenesis is the same regardless of the etiology-a decrease in enteric perfusion that results in enteritis, dysmotility, necrosis, and sepsis. This study aims to evaluate whether the characteristics of NEC in infants with congenital heart disease (CHD) are different from those of classical NEC. The records of 39 NEC patients were reviewed retrospectively. Based on the presence or absence of CHD, the patients were divided into two groups. The group with NEC and CHD was named cardiogenic NEC and the other group was named classical NEC. The two groups were compared in terms of mode of delivery, gestational age, birth weight, age at onset of NEC, surgical treatment rate, NEC localization, and mortality rate. Results The cardiogenic NEC group consisted of 25 patients, and the classical NEC group consisted of 14 patients. The results indicate that there were no differences between the two groups in terms of sex, mode of delivery, and location of the NEC. There were higher levels of gestational age, birth weight, and age at which NEC was diagnosed in the cardiogenic group. The mortality rate of the cardiogenic NEC group (72%) was higher than that of the classical NEC group (28.6%). In addition, the surgical treatment rate of the cardiogenic NEC group (84%) was higher than that of the classical NEC group (57.2%). Conclusions The clinical course of NECs with CHD is different from that of classical NEC. In NEC, CHD can be identified as an important risk factor.